Pengaruh Variabel Makro Ekonomi Terhadap Jakarta Islamic Indeks Periode Januari 2020 Hingga 2022 - Three Handayani NP; Sella Egita; Juaro A Siregar; Suhairi Ritonga (Maktabatun: Jurnal Perpustakaan dan Informasi, 2023)
This study aims to determine whether there is an influence of macroeconomic variables on the Jakarta Islamic Index (JII) for the period January 2020 to 2022. The population of this study is data obtained from the Central Bureau of Statistics (Inflation), Bank Indonesia (Interest Rates and Exchange Rates), and Indonesia Stock Exchange Statistics (JII). This study uses a quantitative approach, where data is measured on a numerical scale based on time series data related to macroeconomic variables. Based on the table it can be seen that the 3 independent variables, namely BIrate, CPI, and exchange rate partially affect BRIS stock prices with their respective significance levels, namely BIrate of 0.0003, CPI of 0.0001, and Exchange rate of 0.0002 and it can be seen that the calculated F value is 11.94024 with probabilities 0.000. Based on this, it can be concluded that the independent variables jointly influence the Jakarta Islamic Indexes (JII).